Performance of finger joint from Sepetir / Yuhanis Yunus - Yunus, Yuhanis (Faculty Of Applied Sciences, 2015)
This study was conducted to evaluate the effects of pressure on performance of the finger joint. The wood species studied were sepetir (sindofa spp) and adhesives were poly (vinyl acetate) (PVAc).However, there is little information available concerning the bending strength and modulus of elasticity and modulus of rupture for finger joints in these field. In this study, it was aimed to determine the bending strength and modulus of elasticity and modulus of rupture for finger joints. For this purpose, samples were tested according to the ASTM 05572 - 95(2012) standard. The pressure apply on the finger joint is different, 1MPa 2MPa 3MPa. Result of the study 1MPa shown that it is the best pressure can be applied on the joint. It can be concluded that the result of pressure on sepetir wood is match to previous study and suitable to be commercialized.